2012
DOI: 10.5172/conu.2012.42.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Using children’s picture books for reflective learning in nurse education

Abstract: One way in which nursing students may build their practice is through reflective learning from stories. Stories in children's literature offer a special source of narratives that enable students to build empathy and to examine and reconstruct their personal concepts around human experience. Illustrated storybooks written for children are a particularly attractive teaching resource, as they tend to be short, interesting, colourful and easy to read. Yet, little has been written about using such books as a reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
4
0
3
Order By: Relevance
“…Other teaching strategies that incorporate narrative include e.g. reflection (Johns, 2013); story telling (East et al, 2010); use of children's books (Crawley et al, 2012); simulation (Walsh, 2011);and McGrath (2011) found that debriefing sessions provided an opportunity for carers to make meaning around the loss of patients and provided emotional support by giving them 'a place and permission to share their feelings with colleagues and make meaning of loss' (p. 8). Narrative is also used in therapy as a means of constructing meaning from life and death (Neimeyer, 2001).…”
Section: Creative Teaching Methodsmentioning
confidence: 99%
“…Other teaching strategies that incorporate narrative include e.g. reflection (Johns, 2013); story telling (East et al, 2010); use of children's books (Crawley et al, 2012); simulation (Walsh, 2011);and McGrath (2011) found that debriefing sessions provided an opportunity for carers to make meaning around the loss of patients and provided emotional support by giving them 'a place and permission to share their feelings with colleagues and make meaning of loss' (p. 8). Narrative is also used in therapy as a means of constructing meaning from life and death (Neimeyer, 2001).…”
Section: Creative Teaching Methodsmentioning
confidence: 99%
“…Dentro de esta categoría es posible identificar diversos propósitos: desde experiencias y vivencias de los lectores, así como entornos socioculturales y políticos. De este modo, en primer lugar, algunos estudios usan los libros como un medio para referir a las experiencias y vivencias que los lectores "traen" a la lectura (Crawley et al, 2012;Hayik, 2011;Hope, 2016;Kim, 2016b). Crawley et al (2012), por ejemplo, usan libros álbum con estudiantes de enfermería para plantear la temática de la muerte, la que promueve la reflexión crítica de las experiencias, las vivencias, los valores y las actitudes de estos.…”
Section: El Libro áLbum Como Gatillanteunclassified
“…La mayoría de los estudios de esta revisión reportan respuestas asociadas con el pensamiento crítico y de tipo subversivas. Las respuestas de pensamiento crítico suelen referirse a procesos reflexivos de los lectores que permiten a los investigadores asumir que los estudiantes están argumentando de forma crítica (Crawley et al, 2012;Korteweg et al, 2010). Por otro lado, muchos estudios reportan respuestas creativas de los estudiantes como evidencia de que estos han llegado a un nivel más avanzado de habilidades críticas, ya que la creación es considerada como la subversión del contenido de los libros (Ko, 2013;Hayik, 2011Hayik, , 2015Hope, 2016;Kim, 2014Kim, , 2016bMurris y Thompson, 2016).…”
Section: Estudios Que Reportan Respuestas Críticas Y Subversivasunclassified
“…Life reviews could be combined with creating a scrapbook or other tangible product that the patient and family could keep once the course has ended. 3,25 Implications for Nursing Education RNs believe they are inadequately prepared to handle the complex nature of end-of-life care in clinical practice. 24 Literature as a teaching strategy is also considered; students who read about patient or family experiences may gain a deeper understanding of the dying experience.…”
Section: Course Evaluation and Future Recommendationsmentioning
confidence: 99%